PENDIDIKAN KARAKTER PERSPEKTIF IBNU MISKAWAIH - Mulkul Farisa Nalva (PAI RAFAH, 2020)
Character education is an education that is very urgent to discuss because various kinds of problems related to character such as social deviations in children certainly give a hard slap to educators, especially Islamic education. Education is an effort made by someone to make changes for the better. Education thinking according to Ibn Miskawaih aims that education is not only a transfer of knowledge but is accompanied by a transfer of values. This research is a type of library research. The data collection uses the documentation method. Data analysis uses descriptive qualitative methods. By using the study literature of research results obtained according to Ibn Miskawaih, education is based on noble character or noble ethics with the ultimate goal that one will feel happiness in the world or the hereafter. The concept of education offered by Ibn Miskawaih is known as the middle way. He revealed that the basic character of humans is restraint, courage, wisdom, and justice. Ibnu Miskawaih views education as a means to make students' subjects noble not just to have high knowledge. According to Ibn Miskawaih, basic education with noble character or noble ethics with the ultimate goal is that one will feel happiness in the world or the hereafter. The concept of education offered by Ibn Miskawaih is known as the middle way. He revealed the basic character of humans who hold back, challenge, refute, and justice. Ibnu Miskawaih views education as a means to make students' subjects fortunate not just to have high knowledge.